Pengaruh Gaya Kepemimpinan Transformasional Dan Komitmen Karyawan Terhadap Kinerja Karyawan Pada PT. Bank Rakyat Indonesia, Tbk KCP Puruk Cahu - Eka Puji Riastuti; Saladin Ghalib; Irwansyah Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2018)
This study aims to identify and analyze the partial and simultaneous the style of transformational leadership and employee commitment to employee performance at PT. Bank Rakyat Indonesia, Tbk KCP Puruk Cahu simultaneously or partially.The study population was 31 respondents in which the sample of the study was determined by saturation sampling so that all members of the population became the research sample. Data were collected by questionnaire which then the result was analyzed by using multiple linear regression analysis.The results showed that partially transformational leadership (X1) on employee performance (Y) showed that the value of t arithmetic of 0.482 with probability of 0.634. The test results prove transformational leadership (X1) have a significant effect on employee performance (Y) with a large influence of 10.3%. In addition, partially employee commitment (X2) to employee performance variable (Y) shows that the value of t arithmetic of 2.782 with a probability of 0.010. The test results proved employees' commitment (X2) has a significant effect on employee performance (Y) with a large influence 59.5%. It also makes employee commitment (X2) to be the dominant variable in influencing employee performance. Simultaneously, transformational leadership (X1) and employee commitment (X2) have an effect on employee performance (Y) equal to 41,9%. The remaining 48.1% is influenced by other variables outside the research model. The regression equation formed is Y = 0.811 + 0.125 (X1) + 0.716 (X2) + e.Keywords   :          Transformational Leadership, Employee Commitment, Employee Performance